Sykepleieres erfaringer med samhandlingsreformen ved korttidsavdelinger på sykehjem - Killie, Paul A.; Debesay, Jonas (Nordisk tidsskrift for helseforskning, 2016)
Nurses’ experiences with the coordination reform at short-term wards in nursing homes The Coordination Reform came into force on January 1 2012, as a result patient responsibilities shifted from the hospitals to primary health care. Short-term wards at nursing homes was an essential contributor to the shift, because it entailed that they would receive patients ready for discharge from the hospital at an earlier stage than previously. The aim of this study is to investigate nurses’ experiences in the wake of the Reform and how it affected their work at short-term wards. Nurses’ role in the short-term ward has changed in several areas. The Reform has increased time pressure, a need for increased competence as well as influencing the cooperation between primary health care and hospitals.